2004
DOI: 10.1007/s00221-003-1695-y
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation driving functional improvements and cortical changes in subjects with stroke

Abstract: It has been proposed that somatosensory stimulation in the form of electromyographically triggered neuromuscular electrical stimulation (NMES) to the peripheral nerve can influence functional measures of motor performance in subjects with stroke and can additionally produce changes in cortical excitability. Using a controlled, double-blind design, we studied the effects of intensive (60 h/3 weeks) treatment at home with NMES compared with a sham treatment, applied to the extensor muscles of the hemiplegic fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
233
2
9

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 272 publications
(248 citation statements)
references
References 62 publications
4
233
2
9
Order By: Relevance
“…Cauraugh et al 17 , using the same test, reported a gain of 129% in the FES group, significantly higher than the control group. Kimberley et al 18 found a significant gain in the performance of the Box and Block Test and in subtests of the Jebsen Taylor Hand Function Test only for the FES group. according to the quality of the results of the reviewed articles, there is moderate evidence of the effects of FES on manual dexterity.…”
Section: Manual Dexteritymentioning
confidence: 98%
See 4 more Smart Citations
“…Cauraugh et al 17 , using the same test, reported a gain of 129% in the FES group, significantly higher than the control group. Kimberley et al 18 found a significant gain in the performance of the Box and Block Test and in subtests of the Jebsen Taylor Hand Function Test only for the FES group. according to the quality of the results of the reviewed articles, there is moderate evidence of the effects of FES on manual dexterity.…”
Section: Manual Dexteritymentioning
confidence: 98%
“…Four studies 7,[17][18][19] had a sample with chronic stroke diagnosis, with post-lesion peri- ods varying from 1 17 to 4 ½ years 18 . Sample size varied from 9 11 to 48 10 subjects divided between treatment and control groups.…”
Section: Participants' Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations